CORNEL ŢĂRANU – VALENTIN STREINU: MUSICAL-POETIC CONNECTIONS - Ciprian Gabriel POP (Studia Universitatis Babeş-Bolyai. Musica)
The present article offers a brief overview of the ways poetry is mixed with music in the work Saturnalia (Romanian: Saturnalii) by Cornel Tăranu. A non-exhaustive analysis is thus featured of the particular methods leading to the melody-lyrical results. The analysis focuses on the following coordinates: the idea of continuous variation as a developing principle of musical discourse; the idea of sonorous material – from the point of view of its development, of rhythm, of form used to elaborate on structures and of the type of accompaniment as supporting the poetic aura.